A silver-functionalized metal–organic framework with effective antibacterial activity - Wu, Ya-Meng; Zhao, Pei-Chen; Jia, Bin; Li, Zhe; Yuan, Shuai; Li, Cheng-Hui (New journal of chemistry, 2022)
Ag nanoparticles have attracted wide research interest due to their broad spectrum of antimicrobial activities. However, Ag nanoparticles are prone to aggregate, which decreases the accessible surface area and diminishes the antibacterial activity. Herein, a metal–organic framework with alkene-functional groups was constructed and postsynthetically modified with Ag( i ) for antibacterial applications. The Ag@Zn-MOF exhibits high antibacterial activity toward E. coli and S. aureus , which reaches ∼100% bacterial reduction at a concentration as low as 25 μg MOF cm −3 (corresponding to 1.7 μg Ag cm −3 ). These results demonstrated that Ag( i )-modified MOFs could act as effective antimicrobial agents with potential applications in food and healthcare.